Refusing Detroit’s public school failure: African American women’s educational advocacy and critical care versus the politics of disposability - Wilson, Camille M (Education Policy Analysis Archives, 2015)
This article highlights a narrative study of African American women educational advocates in Detroit and the political resistance they enact to combat the inequities of structural educational failure and disempowering neoliberal dynamics. The Detroit advocates have challenged the traditional public educational system as volunteers, family members, community activists, elected officials, and/or professional educators. The author discusses the advocates’ perspectives, experiences, and improvement strategies in light of Detroit’s complex, market-based educational landscape. Findings pertain to the advocates’ efforts to respond to educational and communal loss, family engagement barriers, insufficient school choice options, and concerns about privatization. Their narratives comprise counter-stories that illustrate theoretical notions of critical care and traditions of Black women’s political resistance used to combat the politics of disposability that hinder many urban communities. The author concludes the article by indicating how the Detroit advocates’ work can inform broader efforts to improve urban education.